Profile of Antidepressant Use and Drug Interactions among Psychiatric Outpatients at RSUD Ainun Habibie - Nabila Husnunnisa Ismail; Teti Sutriyati Tuloli; Nur Rasdianah; Mohamad Aprianto Paneo (Journal of Experimental and Clinical Pharmacy (JECP), 2026)
Mental disorders are commonly treated with antidepressants, antipsychotics, or their combination. Although combination therapy may improve therapeutic outcomes, it also increases the risk of potential drug–drug interactions (DDIs), which can affect drug efficacy and safety. This study aimed to evaluate the prescribing profile of antidepressants and the potential DDIs among patients attending the Mental Health Outpatient Clinic at Ainun Habibie Hospital. A retrospective descriptive study was conducted using medical records. Patients were selected through purposive sampling, and 161 records met the inclusion criteria. Potential DDIs were identified and classified according to their mechanism and severity. Of the 161 medical records reviewed, 160 patients (99.38%) had at least one potential DDI. A total of 479 potential interactions were identified, including 116 (24.22%) pharmacokinetic and 364 (75.83%) pharmacodynamic interactions. Pharmacodynamic interactions consisted of 353 (73.54%) synergistic and 11 (2.29%) antagonistic effects. Based on severity, 106 (22.13%) interactions were classified as major, 371 (77.45%) as moderate, and 2 (0.42%) as minor. The most common potential DDIs were clozapine–fluoxetine (44 cases, 9.17%), Merlopam–Sandepril (42 cases, 8.75%), and trihexyphenidyl–risperidone (38 cases, 7.92%). Potential DDIs were highly prevalent among psychiatric outpatients, with pharmacodynamic interactions of moderate severity predominating. Routine medication review and monitoring are essential to reduce the risk of clinically significant DDIs and improve patient safety.